(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study purpose of the study was to compare the extent of Self-Concept between junior Modern martial arts players (Junior Karate¬-do players) and Ancient Martial Arts Players (Junior Kalaripayattu participants) of Uttar Pradesh and Kerala respectively. Martial Art is a common type of fighting skills. The origin of martial art is difficult to trace. There are several types of martial arts in this world prevailing, i.e., percussive and non-percussive. Karate-do represents a method of unarmed self- defense based on the rational use of all body parts. The Subjects were selected randomly using Random sampling technique. Players selected from both states were divided in two groups Karate-do Group (N=100) and Kalaripayauttu Group (N=100). Self-Concept Questionnaire was administered, which included 48 test items in 8 separate dimensions of Self Concept. The subjects age range was from 14-18 years. Result of the study indicates that statistically significant difference in self-concept was observed between Ancient Martial Arts and Modern Martial Arts Players.